Stratum Corneum as a Sampling Matrix for Biomarker-Based Assessment of Solar Ultraviolet Exposure among Outdoor Workers - Freade Akbar; Muhammad Ilyas (ILUNI MKK FKUI and PRODI MKK FKUI, 2026)
Introduction: Outdoor workers experience substantial solar ultraviolet radiation (UVR) exposure, yet related occupational skin diseases remain under-recognized. Early identification of biological changes induced by UVR is important for prevention. The stratum corneum (SC), the outermost epidermal layer, contains biochemical components responsive to UVR and can be sampled non-invasively, suggesting its potential as a biomarker source.Methods: We conducted a structured literature review using major scientific databases focusing on UVR exposure, occupational health, and SC-based biomarkers. Papers describing the physiology of UVR exposure, established measurement methods, occupational risk profiles, and potential SC biomarkers, including urocanic acid (UCA) isomers and immunological mediators, were evaluated based on relevance and methodological rigor. Results: Solar UVR, classified as a Group 1 carcinogen, induces acute and chronic skin effects. Outdoor workers receive cumulative UVR doses two to four times higher than indoor workers. Tape stripping enables minimally invasive SC collection suitable for biochemical, microscopic, and immunological analysis. Among potential markers, the trans- to cis-urocanic acid isomerization ratio demonstrates consistent UVR-dose responsiveness and correlates with exposed anatomical sites. Several cytokines involved in inflammation and UVR-induced immunomodulation may complement UCA analysis, although their consistency across studies varies.Conclusion: The SC provides a practical matrix for assessing solar UVR exposure among outdoor workers. UCA isomer ratios represent the most promising SC biomarker, supported by mechanistic and empirical evidence. Standardization of sampling, analysis, and interpretation is required before incorporation into occupational surveillance programs.